The effect of lycopene supplementation on chronic obstructive lung disease - Kirkil, Gamze; Muz, Mehmet Hamdi; Sancaktar, Enver; Kaman, Dilara; Şahin, Kazım; Küçük, Ömer (My University, 2012)
Objective: An imbalance in the oxidant-antioxidant system has been recognised as one oj the first events that ultimately lead to inflammatory reactions in chronic obstructive lung disease (COPD). Lycopene, an antioxidant carotenoid, is associated with prevention of some human chronic diseases. This study was designed to investigate the effect of lycopene on oxidant stress and pulmonary function tests (PFT) in patients with COPD. Material and Method: Thirty clinically stable COPD patients, and 15 healthy non-smoker subjects were enrolled on the study. Fifteen COPD patients received oral placebo and 15 patients received 20 mg lycopene daily for 4 months in addition to their standardized therapy. Their baseline spirometry, plasma malondialdehyde QADA), superoxide dismutase (SOD), catalase (CAT), interleukin (IL)-6, IL-1?, and tumor necrosis factor alpha (TNF-? levels) were measured in serum. All parameters were measured again after supplementation. Results: The mean MDA, IL-6, IL-1?, and TNF-? levels in the COPD group at baseline were higher than controls, while SOD and CAT levels were lower in the patients compared to controls. Four months of lycopene supplementation produced significant increase in mean SOD, and CAT levels (both p<0.001), significant decrease in mean MDA, IL-6, IL-1?, and TNF-? levels (p=0.001, p<0.001, p=0.002, p<0.001, respectively). Although no significant change in forced expiratory volume in one second (FEV,) (% predicted) was observed after lycopene supplementation, FEV/FVC (%) ratio was increased (p=0.016). Conclusion: The results suggest that lycopene supplementation may have favorable effects on oxidantantioxidant balance in patients with COPD.
Keywords: Antioxidants; Copd; Lycopene; Oxidants